(untitled) (Journal of Orofacial Research, 2020)
Background: Spontaneous bacterial peritonitis (SBP) is a frequent complication of cirrhosis resulting from factors like bacteraemia and defective ascitic fluid bactericidal activity. Also, bacteraemia is more common in patients with poor oral hygiene. Objective: To assess the association of SBP and poor oral hygiene in cirrhotic patients with ascites. Methods: A cross-sectional study was conducted among Forty-three cirrhotic patients with ascites admitted in Gastroenterology department of a tertiary care centre in central Kerala between November 2017 and July 2018. Patients were divided into 2 groups (good and poor oral Hygiene) using the simplified Oral Hygiene Index (OHI-S). Paracentesis was done and a neutrophil count of >250/cm2 was considered as diagnostic of SBP. Results: Of the 43 patients studied, 17 patients had poor oral hygiene and 26 patients had good oral hygiene. The association of SBP with poor oral hygiene was observed in 12 (70.6%) patients, while 2 patients with good oral hygiene had SBP (p < 0.0001). Poor oral hygiene was more common in patients with higher MELD (Model for end stage liver disease) scores. However even in patients with higher MELD scores (>10), SBP was more common in patients with poor oral hygiene (81.8 vs 16.7 %). Conclusion: SBP was more common in cirrhotic patients with ascites and poor oral hygiene. Further prospective studies are needed to determine whether improving oral hygiene can reduce the incidence of SBP.